Gallbladder perforation during elective laparoscopic cholecystectomy: Incidence, risk factors, and outcomes - Altuntaş, Yunus Emre; Öncel, Mustafa; Haksal, Mustafa; Kement, Metin; Gündoğdu, Ersin; Aksakal, Nihat; Gezen, Fazlı Cem (Kare Publishing, 2018)
OBJECTIVE: This study aimed to reveal the risk factors and outcomes of gallbladder perforation (GP) during laparoscopic cholecystectomy. METHODS: Videotapes of all patients who underwent an elective cholecystectomy at our department were retrospectively analyzed, and the patients were divided into two groups based on the presence of GP. The possible risk factors and early outcomes were analyzed. RESULTS: In total, 664 patients [524 (78.9%) females, 49.7 +/- 13.4 years of age] were observed, and GP occurred in 240 (36.1%) patients, mostly while dissecting the gallbladder from its bed (n=197, 82.1%). GP was not recorded in the operation notes in 177 (73.8%) cases. Among the studied parameters, there was no significant risk factor for GP, except preoperatively elevated alanine transaminase level (p=0.005), but the sensitivity and specificity of this measure in predicting GP were 14.2% and 7.4%, respectively. The two groups had similar outcomes, but the operation time (35.4 +/- 17.5 vs 41.4 +/- 18.7 min, p=0.000) and incidence of drain use (25% vs 45.8%, p=0.000) increased in the GP group. CONCLUSION: The present study reveals that GP occurs in 36.1% of patients who undergo laparoscopic elective cholecystectomy, but it may not be recorded in most cases. We did not find any reliable risk factor that increases the possibility of GP. GP causes an increase in the operation time and incidence of drain use; however, the other outcomes were found to be similar in patients with GP and those without.
WOS: 000433094100010
PubMed ID: 29607432
Keywords: Alanine Transaminase; Gallbladder Perforation; Laparoscopic Cholecystectomy